Anaerobic power and muscle work capacity of Lithuanian basketball players - Paulauskas, R. (LASE Journal of Sport Science, 2013)
Basketball players need to repeat performance of highly intensive work for a particular time combining them with rest intervals. However, the anaerobic power and repetitive work capacity of players has not been extensively analysed all over the world. The aim of our study is to investigate anaerobic power and specific capacity of elite and young basketball players. Methods. During competition period the indicators of anaerobic power of basketball players were measured: vertical jump power, anaerobic alactic muscular power, anaerobic capacity of intermittent work. Laboratory 5x6 second repeat-effort test with rest intervals of 24 sec were employed. Results. A statistically significant difference was observed for absolute muscle power of elite and young basketball players in the first sprint (p<0.004). The research on relative indicators for one kilogramme of the body mass showed that the power of elite (13.06W/kg) and young players (11.74W/kg) did not differ statistically (p<0.09). The fatigue index investigated in both groups did not differ (p<0.77). Conclusions. Vertical jump anaerobic power test showed that Lithuanian elite basketball players have higher jump but a longer contact time during the jump than young athletes. The research revealed that relative anaerobic alactic muscle power of elite basketball players did not differ from those of young (14y.o) and junior (17y.o.) athletes. The same anaerobic repetitive muscle work capacity was observed in both groups. It was established that the concentration of lactate in the blood increased after physical load and did not differ in all groups.